Why Regulate Insider Trading? Evidence from the First Great Merger Wave (1897–1903) - Banerjee, Ajeyo; Eckard, E. Woodrow (American Economic Review, 2001)
We use event-time methodology to study legal insider trading associated with mergers circa 1900. For mergers with “prospective” disclosures similar to today's, we find substantial value gains at announcement, implying participation by “out-side” shareholders despite the absence of insider constraints. Furthermore, preannouncement stock-price runups, relative to total value gain, are no more than those observed for modern mergers. Insider regulation apparently has produced little benefit for outsiders, with the inside information-pricing function and related gains shifting to external “information specialists.” Other results suggest market penalties for nondisclosure; i.e., insider trading is less successful in a restricted information environment. (JEL G3, K2, L5, N2)